EVALUASI KESELAMATAN KERJA DALAM PEKERJAAN BLOK FABRIKASI DI PT KARIMUN SEMBAWANG SHIPYARD DENGAN METODE PENDEKATAN HIRARC - Kurniawan, Doni (UNIMAR AMNI Semarang, 2025)
The number of work accidents in Indonesia continues to increase. Based on BPJS Employment data, the number of cases in 2019 was recorded at 182,835 cases. Furthermore, the number consistently increased, 221,740 in 2020 and 234,370 in 2021. Then in 2022, the number increased again to 297,725. The purpose of this research is to determine the implementation of identifying hazards in block fabrication work at PT. Karimun Sembawang Shipyard using the HIRARC method. The sample of this research was 68 people. Primary data was collected by means of field observation, distributing questionnaires, and documentation. Pay more attention to manual cutting when making blocks, there are several workers who cut close to oxygen hoses and LPG/Acetyline hoses, which causes the hoses to catch fire and can later cause a fire when making ship blocks.